Mass spectrometric identification of diagnostic markers for chronic prostatitis in seminal plasma by analysis of seminal plasma protein clinical samples - Rokka, A.; Mehik, A.; Tonttila, P.; Vaarala, M. (Cellular and Molecular Biology, 2017)
There are few specific diagnostic markers for chronic prostatitis. Therefore, we used mass spectrometry to evaluate differences in seminal plasma protein expression among patients with prostatitis and young and middle-aged healthy controls. We analysed pooled seminal plasma protein samples from four prostatitis patients (two pools), three young controls (one pool), and three middle-aged controls (one pool). The samples were analysed by liquid chromatography–tandem mass spectrometry. Of the 349 proteins identified, 16 were differentially expressed between the two control pools. Five proteins were up- or down-regulated in both of the prostatitis pools compared to middle-aged controls but not between young and middle-aged pools. Progestagen-associated endometrial protein (PAEP) was over-expressed in prostatitis samples compared to young and middle-aged controls. Our findings and those of previous studies indicate that PAEP is a potential seminal plasma marker for chronic prostatitis. In conclusion, we found age-related changes in seminal plasma protein expression. PAEP expression in seminal plasma should be investigated further to evaluate its potential as a diagnostic marker for chronic prostatitis.